Violência de gênero: crenças legitimadoras por adolescentes - Albuquerque, Juliana Rodrigues de (2019)
This thesis aims to analyze the beliefs underlying the legitimacy of gender violence by adolescents. To achieve this goal, this work was organized in three articles, which adopt as theoretical references the Societal Beliefs, Culture of Rape and the sociological currents of Patriarchal Domination and Male Domination. The first article aimed at raising beliefs that legitimize the categories of violence against women according to the Maria da Penha Law. A total of 201 high school adolescents from public and private schools in the city of Joao Pessoa, with an average age of 16, participated. A Free Speech Association Technique (TALP) was used, containing five inductive stimuli and three questions about stimuli, where each stimulus corresponded to a fictional story about a type of violence. Descriptive and inferential statistics were performed. On the evocations, they were analyzed through the computer program IRAMUTEQ. The results pointed to the perception of machismo by the majority of adolescents, in patrimonial violence, to the phenomenon of victim's responsibility in sexual violence, to the justification of physical violence, to blaming women in moral violence and to "romanticizing jealousy "in psychological violence. The second article analyzed the beliefs of gender-based sexual violence. The sample was 201 high school students from public and private schools in the city of João Pessoa, with an average age of 16 years. A Rape Myth Acceptance Scale (IRMA) was applied. Descriptive and inferential statistics were performed. In the "Female Responsibility" factor, adolescents significantly legitimized sexual violence and, through t-test, it was found that in some items, boys and public school students legitimized more. On the "Minimizing of Gravity" factor, the larger average involved the belief that the rape victim must prove that she fought against violence. The "Female Excuse" factor pointed to beliefs related to male aggressiveness as socially expected. And the "male instinct" factor demonstrated the presence of rape beliefs as the cause of uncontrollable male sexual desire. Article 3 aimed to gather evidence of construct validity from the Beliefs Scale for Gender Violence for adolescents. A total of 513 high school students from public and private schools in the city of João Pessoa, with an average age of 16, participated. The Violence Belief Scale of Gender Violence was applied, covering all categories of violence. Descriptive statistics and factor analysis were used, using the Principal Components technique, as well as the Cronbach's Alpha technique. The results showed that the instrument has satisfactory statistical parameters. Given the results presented, it must be understood that gender violence involves a phenomenon of multiple aspects, making it imperative to develop educational strategies aimed at deconstructing legitimating beliefs of gender violence in all its modalities.